"Dark and Dirty" Histories of Leisure and Architecture: Varosha's Past and Future. Issue 1 (2nd January 2020) - Pyla, Panayiota; Phokaides, Petros
Abstract: Once celebrated as a tourist destination, and now filled with derelict hotels, Varosha is a contested landscape at once embodying contradicting political and economic aspirations and featuring vividly in negotiations for political reconciliation in Cyprus. This paper provides a history of the antagonisms that surround this area by interrogating the creation of hotels and landscapes of leisure in 1960s Varosha and by exposing how these aspired to transform the cultural identity of the entire island. Casting the spotlight on the Golden Sands hotel, the paper demonstrates that, along with advancing iconographies of global modernity, hotel design was insidiously shaped by ethnic disputes as well as socio-economic and environmental contestations. Seen in the context of other conflict-torn cities, this history of the contested landscape of Varosha provides crucial insights into the imbrications of architectural history and design practices in the management of contested instances of modern, twentieth-century heritage.